Взаимодействие экономического роста и уровень общественных расходов в контексте закона Вагнера - Афанасьев, Мстислав; Шаш, Наталия (Вопросы государственного и муниципального управления, 2018)
The paper looks into how the law formulated by A. Wagner can be used to stimulate economic growth in a post-crisis period. The major principles of the concept of fiscal economy are given. It is mainly focused on identifying regularities in perpetually growing state spending, which can be explained by increasing the fiscal needs of the state. On the basis of data from 1960 to 2015, this regularity is confi rmed for the G7 countries and Russia. It is shown that state spending goes up mostly due to growing pension payments. The authors present the results of Wagner’s Law testing obtained by researchers based on the analysis of data on both developed and developing countries. It has been discovered that it is impossible to conclude categorically about a positive effect of fiscal stimulation on economic growth. The main factors which affect the efficiency of the applied fi scal measures are described. Russia is given as an example, where the growth of state spending due to an increase in fiscal needs has not made it possible to ensure the necessary economic growth rate due to its low efficiency. The authors have found out that the main cause of the continually growing budget spending is a large share of the state presence in the Russian economy. This slows down the process of its recovery growth, which does not allow for realizing the existing potential. It has been concluded that state spending efficiency must be improved, among other things, due to a structural transformation of state spending in the budgeting system of the RF.